2009
DOI: 10.1002/bjs.6456
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model for local recurrence after transanal endoscopic microsurgery for rectal cancer

Abstract: Patient selection for TEM is frequently governed by fitness for radical surgery rather than suitable tumour biology. TEM can produce long-term outcomes similar to those published for radical total mesorectal excision surgery if applied to a select group of biologically favourable tumours. Conversion to radical surgery based on adverse TEM histopathology appears safe for p T1 and p T2 lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
210
4
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(233 citation statements)
references
References 31 publications
7
210
4
12
Order By: Relevance
“…Stellt sich erst nach transanaler Vollwandresektion eine Hoch-Risiko-Konstellation heraus, so ist die sekundäre radikale Nachoperation innerhalb eines Monats nicht mit einer Verschlechterung der Prognose im Vergleich zum primär radikalen Vorgehen assoziiert [772,776]. Lehnt der Patient in dieser Situation eine radikale Nachoperation ab, so kann eine adjuvante Radiochemotherapie erwogen werden.…”
Section: Hintergrundunclassified
“…Stellt sich erst nach transanaler Vollwandresektion eine Hoch-Risiko-Konstellation heraus, so ist die sekundäre radikale Nachoperation innerhalb eines Monats nicht mit einer Verschlechterung der Prognose im Vergleich zum primär radikalen Vorgehen assoziiert [772,776]. Lehnt der Patient in dieser Situation eine radikale Nachoperation ab, so kann eine adjuvante Radiochemotherapie erwogen werden.…”
Section: Hintergrundunclassified
“…LE has also been proposed in frail patients or in those refusing major surgery to remove more invasive rectal cancers (T1 sm2-3 and T2). However, the risk of recurrence is significantly higher, and therefore LE alone should be considered only as a compromise procedure [89][90][91][92]. The use of neoadjuvant (chemo)radiation therapy followed by full thickness LE of more advanced T1 and T2…”
Section: Qualitative Risk Factors and New Biomarkersmentioning
confidence: 99%
“…On the other hand, the published results on the oncological outcome following TEM remain controversial, since other studies [85] reported favorable results with local recurrence rates lower than 10%, others [86] confirmed the lower local recurrence rates following TEM compared to the transanal local excision (18.5% vs 27.7%) but without statistical significance, others [87] stated alarming figures for local recurrence following TEM for T1 rectal tumors, while local recurrence rates as high as 20.5% have also been reported [88] . In an attempt to evaluate further the above findings, both Tytherleigh et al [89] in 2008, as-well-as Bach et al [90] in 2009, offered possible explanations for these unfavorable results. Both studies made clear that the depth of submucosal invasion (sm level) constituted a strong predictor for recurrence, since sm1 tumors showed low recurrence rates, but sm2-3 tumors showed recurrence rates similar to the T2 lesions [89,90] .…”
Section: Long-term Results Studies On the Oncological Outcome Followimentioning
confidence: 96%
“…In an attempt to evaluate further the above findings, both Tytherleigh et al [89] in 2008, as-well-as Bach et al [90] in 2009, offered possible explanations for these unfavorable results. Both studies made clear that the depth of submucosal invasion (sm level) constituted a strong predictor for recurrence, since sm1 tumors showed low recurrence rates, but sm2-3 tumors showed recurrence rates similar to the T2 lesions [89,90] . Thus, locally excised pT1sm1 tumors without lymphovascular invasion, up to 3 cm in diameter, have a local recurrence rate of less than 5%, while locally excised pT1sm2-3 tumors have a local recurrence rate of up to 20%, similarly to T2 tumors [72] .…”
Section: Long-term Results Studies On the Oncological Outcome Followimentioning
confidence: 96%